Healthcare‐associated infections, medical devices and biofilms: risk, tolerance and control. Issue 4 (April 2015) - Percival, Steven L.; Suleman, Louise; Vuotto, Claudia; Donelli, Gianfranco
Abstract : N/A: Biofilms are of great importance in infection control and healthcare‐associated infections owing to their inherent tolerance and 'resistance' to antimicrobial therapies. Biofilms have been shown to develop on medical device surfaces, and dispersal of single and clustered cells implies a significant risk of microbial dissemination within the host and increased risk of infection. Although routine microbiological testing assists with the diagnosis of a clinical infection, there is no 'gold standard' available to reveal the presence of microbial biofilm from samples collected within clinical settings. Furthermore, such limiting factors as viable but non‐culturable micro‐organisms and small‐colony variants often prevent successful detection. In order to increase the chances of detection and provide a more accurate diagnosis, a combination of microbiological culture techniques and molecular methods should be employed. Measures such as antimicrobial coating and surface alterations of medical devices provide promising opportunities in the prevention of biofilm formation on medical devices.